China-India Rivalry in Health Diplomacy: Issue in South Asia - Tanwar, Priyanka (Asian Journal of Pharmaceutics (AJP), 2023)
This paper focuses on China-India rivalry in health diplomacy in South Asia. To increase their geopolitical influence particularly in South Asia, both countries continue to prioritize health diplomacy in their foreign policies. China was given the responsibility for starting COVID-19, but concurrently, the same nation had taken advantage of the global-health crisis using its health diplomacy at global level as a soft power instrument for expanding its strategic influence in terms of hegemony. The paper also highlights the tussle between India and China for strategic influence in South Asia. This paper examines India and China’s global health diplomacy during COVID-19 particularly in South Asia. According to author, both countries compete with each other in South Asia. The author concludes that China utilized the COVID situation better than India to improve its relations with South Asian countries.